88.6k views
1 vote
(14 + 6) + 11 Which of the following is equal to the expression listed above? A. (14 + 6) + (6 + 11) B. (14 + 6) × 11 C. 11 × 14 + 11 × 6 D. 14 + (6 + 11)

2 Answers

5 votes

Answer:

The answer is D.

Explanation:

(14 + 6) + 11 is equal to 14 + (6 + 11). The associative property of addition was used, which is when the equation is the same no matter how it is grouped.

(14 + 6) = 20, and 20 + 11 = 31.

(6 + 11) = 17, and 14 + 17 = 31.

They were grouped differently, but they had the same sum.

I hope this helped! :-)

User Enrico Campidoglio
by
5.8k points
2 votes
D. 14 + (6 + 11) = 31
User Littin Rajan
by
5.7k points